Angelo Patri papers - Patri, Angelo, 1876-
Correspondence, writings, radio scripts, biographical material, financial records, and other papers reflecting Patri's role as an educator and popularizer of John Dewey's progressive educational principles. Traces the evolving nature of education and child rearing from the 1920s to the 1960s. Patri's writings on children include typewritten copies of his syndicated column "Our Children." Also includes a draft of his unpublished autobiography pertaining to his years as a public school principal in New York City and correspondence with parents seeking Patri's child rearing advice.
Library of Congress Prints and Photographs Division.
Educator and author. Died 1965.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Dewey, John, -- 1859-1952.; Child rearing; Children; Education; Education -- New York (State) -- New York; Newspapers -- Sections, columns, etc; Progressive education; Radio scripts; School principals -- New York (State) -- New York; Public schools -- New York (State) -- New York; Authors; Educators